Karakterisitk Pantulan Spektral Citra Landsat 8 Pada Area Pasang Surut: Studi KasusTeluk Benoa, Bali - Karang, I Wayan Gede Astawa (Journal of Marine and Aquatic Sciences; Vol 2 No 2 (2016), 2016)
Benoa bay is a tidal area located in the southern part of Bali island. Several study of physical aspect of sea water in the Benoa bay has been done using remote sensing data. At this moment there aren’t studies about the relationship between the tidal condition and the spectral response. For this reason, the aim of this work is to study the characteristic of spectral response of satellite data linked to tidal variation. To meet the goal, Landsat TM 8 images were used in eight different dates ranging from March 2014 to May 2015. The methodology included techniques such as radiometric corrections, cropping and statistical analysis for band 1 to 7. The results indicate that when landsat 8 images acquired, Benoa Bay has a tidal elevation from -0.121 to 0.857. The spectral responses for the sea water body show a contrast between the visible and infrared regions. There isn’t clear correlation between tidal water variation and its spectral behavior of infrared regions; it depends rather on the presence or absence of sediments and vegetation in the water as shown in the visible region with moderate correlation 0.65 (Band 1) and 0.67 (Band 2).
Keywords: Benoa bay; remote sensing; spectral response; tidal elevation